The effects of Quiet eye training on the performance of in-phase and anti-phase patterns of bimanual coordination in children with DCD - Norouzi Seyed Hosseini, Rasoul; Norouzi, Ebrahim; Soleymani, Mehran (Iranian Journal of Child Neurology, 2021)
Objectives: The Quiet eye training (QET) with the latest techniques as an uncomplicated approach has recently entered the field of research, has drawn the researchers’ attention. Therefore, the objective of this study was to examine the effects of quiet eye training on the perform in-phase and anti-phase patterns of bimanual coordination in children with DCD. Materials & Methods: Participants (n=20; aged 8-9 years) were randomly divided into two groups including traditional training (TT) and QET. The participants performed bimanual in-phase and anti-phase movements with their wrists at three levels of speed ranging from slow to fast. Results: Results showed that there is a significant difference between pre-test and post-test in QET group (P=0.001) and bimanual coordination accuracy in post-test phase have increased significantly compared to pre-test (F=5.66). Moreover, there is a significant difference between pre-test and post-test in bimanual coordination accuracy in TT group (P=0.01) and post-test accuracy significantly increased (F=2.32) but increasing is less than QET group. Discussion: Results indicated that the performance of the in-phase and anti-phase coordination mode was strongly influenced by the QET, and we conclude that a successful performance of a bimanual linear task dependents mainly on the availability of visual feedback.